The bone mesenchymal stem cell-derived exosomal miR-146a-5p promotes diabetic wound healing in mice via macrophage M1/M2 polarization - Zhou, Xijie; Ye, Chenhao; Jiang, Liangfu; Zhu, Xuwei; Zhou, Feiya; Xia, Meizi; Chen, Yiheng (Molecular and cellular endocrinology, 2024)
A diabetic wound is a refractory disease that afflicts patients globally. MicroRNA-146a-5p (miR-146a-5p) is reported to represent a potential therapeutic target for diabetic wounds. However, microRNA easily degrades in the wound microenvironment. This study extracted bone marrow mesenchymal stem cell (BMSC)-derived exosomes (EXO). Electroporation technology was used to load miR-146a-5p into EXO (labeled as EXO-miR-146a). The endothelial cells (human umbilical vein endothelial cells [HUVECs]) and macrophages were cocultured in transwell chambers in the presence of high glucose. Cell proliferation, migration, and angiogenesis were measured with cell counting kit 8, scratch, and tube forming assays, respectively. Flow cytometry was introduced to validate the biomarker of macrophages and BMSCs. The expression level of macrophage polarization-related proteins and tumor necrosis factor receptor-associated factor 6 (TRAF6) was assessed with western blotting analysis. The full-thickness skin wound model was developed to verify the in vitro results. EXO-miR-146a promoted the proliferation, migration, and angiogenesis of HUVECs in the hyperglycemic state by suppressing the TRAF6 expression in vitro. Additionally, EXO-miR-146a treatment facilitated M2 but inhibited M1 macrophage polarization. Furthermore, EXO-miR-146a enhances reepithelialization, angiogenesis, and M2 macrophage polarization, thereby accelerating diabetic wound healing in vivo. The EXO-miR-146a facilitated M2 macrophage polarization, proliferation, migration, and angiogenesis of HUVECs through TRAF6, thereby ameliorating intractable diabetic wound healing. These results established the basis for using EXO to deliver drugs and revealed mediators for diabetic wound treatment. •HG-induced macrophage M1 polarization inhibited HUVEC proliferation, migration, and angiogenesis.•EXO-miR-146a improved the functions of HUVECs in the presence of HG.•EXO-miR-146a induced macrophages from M1 to M2 polarization in the presence of HG.•EXO-miR-146a accelerated diabetic wound healing in vivo.•EXO-miR-146a exerted its roles by modulating the expression of TRAF6.